COVID-19 and heterogeneous vulnerabilities in the Peruvian labor market: implications for social inequalities and for gender gaps - Durán Fernández, Rosa Luz (2021)
Using quarterly data from the 2020 Peruvian National Household Survey (ENAHO), this paper estimates the diferentiated impacts of the COVID-19 pandemic on a set of labor market indicators, such as labor participation, occupational categories, informality, and number of hours worked. The impacts are calculated from an individual perspective (efects on the activities of the heads of household and their spouses, distinguishing them according to sex) and also from a joint strategy perspective among the partners. The results indicate that the intersectionalities of vulnerability considered (rural/urban area, and those contained in the type of households and in the situation of single-parenting or two-parenting of household heads and their spouses) determine that women, who live in rural areas, have children and do not have a partner were the most afected by the global health crisis.